Non-Linear Presentation On Student Performance: Applying Prezi On Engineering Education - Lantana Dioren Rumpa (Neutrino, 2018)
Today there are so many methods of doing presentations. Some of them using digital media as framework. As we know there are too many tools we can used in digital form. One of them is PowerPoint developed by Microsoft. But PowerPoint is a sequencing (Linear) Media. In this paper we tried to explore Non-Linear Media like prezi. Prezi is one of Non-Linear tools to create a presentation based on Cloud Computing. Engineering Education has similarity with other field. Differences between engineering subject with other is structured Course Material. So, we tried to gather some information whether prezi could do the same performance on Engineering Field. Our paper show that there no significant difference between Linear and Non-LinearMedia according to prevoius research. So we can say that we can use prezi as media in Engineering Education.